Knowledge legitimacy battles in nursing, quality in care, and nursing professionalization. Issue 2 (15th February 2022) - Ernst, Jette; Tatli, Ahu
Abstract: The article explores the shifting value of nursing work in the context of knowledge legitimacy battles, policy, and nursing professionalization. We unpack the battle for legitimacy between two approaches to nursing, that is, caring and curing that are associated with traditional and scientific knowledge, respectively, based on an ethnographic study of day-to-day nursing in a new acute care hospital department. The article offers an expansion to the study of professional work and professionalization by using concepts from Bourdieu as a toolkit to bridge structural and subjective dimensions of professional practice when we connect nurses' local experiences of work to macro-level political agendas and nursing professionalization struggles. Our study shows that curing is becoming a nursing domain, and scientific evidence-based knowledge is seen as more legitimate in relation to care quality and nursing professionalization in the healthcare field. We discuss under-recognized consequences of the knowledge legitimacy battles for the organization of care, including nurses' bodywork.